153k views
3 votes
Can you help me simplify the radical expression and leave it in the radical form?

Can you help me simplify the radical expression and leave it in the radical form?-example-1

1 Answer

2 votes

SOLUTION

Given the question in the image, the following are the solution steps to answer the question.

STEP 1: Write the given expression


√(45n^5)

STEP 2: Simplify the expression


\begin{gathered} \mathrm{Apply\:radical\:rule:\:}√(ab)=√(a)√(b),\:\quad \mathrm{\:assuming\:}a\ge 0,\:b\ge 0 \\ √(45n^5)=√(45)√(n^5) \\ =√(45)√(n^5) \end{gathered}

Simplify in units


\begin{gathered} √(n^5)=n^2√(n) \\ √(45)=√(9\cdot5)=√(9)\cdot√(5)=3√(5) \end{gathered}

Combine the solutions to have:


=3√(5)n^2√(n)

Hence, the answer is given as:


\begin{equation*} 3√(5)n^2√(n) \end{equation*}

User Ravi K Thapliyal
by
5.2k points